2017
DOI: 10.3171/2016.6.jns16496
|View full text |Cite
|
Sign up to set email alerts
|

Association between shunt-responsive idiopathic normal pressure hydrocephalus and alcohol

Abstract: OBJECTIVE Idiopathic normal pressure hydrocephalus (iNPH) is characterized by ventriculomegaly, gait difficulty, incontinence, and dementia. The symptoms can be ameliorated by CSF drainage. The object of this study was to identify factors associated with shunt-responsive iNPH. METHODS The authors reviewed the medical records of 529 patients who underwent shunt placement for iNPH at their institution between July 2001 and March 2015. Variables associated with shunt-responsive iNPH were identified using bivariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 36 publications
(62 reference statements)
0
14
1
Order By: Relevance
“…Alcohol consumption was recently suggested to be a potential risk factor for iNPH in two studies [14,67]. Our results don't back up this finding, but it must be noted that our questionnaire represents only the time close to the diagnosis and not their alcohol consumption earlier in life.…”
Section: Alcohol Sleep Apnea Sfmbt1 and Apoe ε4contrasting
confidence: 72%
“…Alcohol consumption was recently suggested to be a potential risk factor for iNPH in two studies [14,67]. Our results don't back up this finding, but it must be noted that our questionnaire represents only the time close to the diagnosis and not their alcohol consumption earlier in life.…”
Section: Alcohol Sleep Apnea Sfmbt1 and Apoe ε4contrasting
confidence: 72%
“…Furthermore, oral intake of ethanol was reported to decrease the beating frequency of motile cilia on the ependymal cells of lateral and third ventricles in a rat model [ 61 ]. Recently, two case-control studies provided evidence indicating that alcohol consumption showed a higher frequency in iNPH patients compared with an age-matched general population [ 62 , 63 ]. Therefore, alcohol consumption is a potential risk factor for developing iNPH due to motile cilia dysfunction on the ependymal cells.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrocephalus, gait dysfunction, incontinence, and dementia that characterize iNPH usually appear after the age of 60, with most iNPH patients being asymptomatic and behaviorally normal prior to disease onset ( 1 , 2 ). We recently reported that loss-of-function deletions in CWH43 are enriched among patients with sporadic iNPH and cause an iNPH-like syndrome in genetically engineered mice ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the congenital hydrocephalus and developmental abnormalities that are frequently seen with L1CAM mutations, iNPH manifests late in life in previously asymptomatic individuals ( 2 6 ). Hydrocephalus and gait abnormalities are detectable in CWH43 mutant mice during early adulthood.…”
Section: Discussionmentioning
confidence: 99%